The Role of Religious Courts in Resolving Inheritance Disputes Through Judicial Legal Reasoning: An Analysis of 2024 Court Decisions - Mukhtar; Zuhrah; Mastorat (Lembaga Bale Literasi, 2025)
Inheritance disputes remain one of the most frequently litigated civil cases before Religious Courts in Indonesia, reflecting the complexity of legal relationships among heirs as well as differences in interpreting Islamic inheritance law. Although the Religious Court possesses absolute jurisdiction over inheritance disputes involving Muslims, variations in judicial legal reasoning continue to influence the consistency and quality of judicial decisions. This study aims to analyze the role of the Religious Court in resolving inheritance disputes and examine the legal considerations employed by judges in inheritance cases adjudicated in 2024. The research adopts an empirical juridical approach using statutory, conceptual, and case approaches. Primary data were obtained through interviews and analysis of court decisions, while secondary data were collected from legislation, legal literature, and scholarly publications concerning inheritance law and judicial authority. The findings indicate that the Religious Court performs not only an adjudicative function but also serves as an institution promoting legal certainty, justice, and societal benefit through comprehensive judicial reasoning. Judicial decisions demonstrate that judges integrate statutory provisions, Islamic legal principles, jurisprudence, and sociological considerations to achieve substantive justice. This study contributes to the development of inheritance law by proposing a comprehensive model of judicial reasoning that strengthens consistency in inheritance dispute resolution within Indonesia's Religious Court system.